Fallopian Tube Herniation: An Unusual Complication of Surgical Drain - Lipi Sharma; Alpana Singh; Sruthi Bhaskaran; A. G. Radhika; Gita Radhakrishnan (Hindawi Limited, 2012)
Background. Surgical drains have been used since time immemorial, but their use is not without complications. By presenting this case we aim to describe an uncommon complication of herniation of fallopian tube following the simple procedure of surgical drain removal. Case Presentation. This case describes a 23-year G2P1L1 who underwent an emergency cesarean section for obstructed labor with intraperitoneal drain insertion. The patient had an uneventful postoperative period, drain was removed on day 4, and she was discharged. She presented on day 8 with the complaint of soakage of drain site dressing. On examination an edematous, tubular structure with early sign of necrosis was seen coming out of drain site and a provisional diagnosis of appendix herniation was made. On emergency laparotomy fallopian tube was seen coming out through the drain site and salphingectomy was done. Conclusion. Drains are not a substitute for good surgical technique. Although herniation of intestine, omentum, appendix, gall bladder, and ovary have been reported, we could not find any case of fallopian tube herniation in the literature searched by us.